Lead Extraction of Cardiac Rhythm Devices: A Report of a Single-Center Experience - Azevedo, Ana Isabel; Primo, João; Gonçalves, Helena; Oliveira, Marco; Adão, Luís; Santos, Elisabeth; Ribeiro, José; Fonseca, Marlene; Dias, Adelaide V.; Vouga, Luís; Ribeiro, Vasco Gama (Frontiers in Cardiovascular Medicine, 2017)
Introduction and objectives The rate of implanted cardiac electronic devices is increasing as is the need to manage long-term complications. Lead removal is becoming an effective approach to treat such complications. We present our experience in lead removal using different approaches, analysing the predictors of the use of mechanical extractors/surgical removal. Methods Retrospective analysis of lead extractions in a series of 76 consecutive patients (mean age 70.4±13.8 years-old, 73.7% men) between January 2009 and November 2015. Results 135 leads from permanent pacemakers (single-chamber 19.7%; dual-chamber 61.8%), implantable cardioverter-defibrillators (5.3%) and cardiac resynchronization devices (CRT-P 2.6%; CRT-D 7.9%) were removed, 72.5±73.2months after implantation. 45.9% were ventricular leads, 40.0% atrial, 8.9% defibrillator leads and 5.2% leads in the coronary sinus; 64.4% had passive fixation. The most common indications for removal were pocket infection (77.8%), infective endocarditis (9.6%) and lead dislodgement (3.7%). 76.3% of the leads were explanted, 20.0% were extracted and 3.7% were surgically removed. Extraction of the entire lead was achieved in 96.3% of the procedures. After logistic regression (age adjusted), time since implantation was the sole predictor of the need of mechanical extractors/surgical removal. All patients were discharged without major complications. There were no deaths at 30-days. Conclusions Our experience in lead removal was effective and safe. Performing these procedures by experienced electrophysiologists with an adequate cardiothoracic surgery team on standby to cope with any complications is required. Referral of high-risk patients to a high volume centre is recommended to optimize clinical success and minimize procedural complications.